Rainfed farming systems - Tow, Philip (Springer, 2011)
While agriculturists need a good grasp of the many separate aspects of agriculture, it is essential that they also understand the functioning of farming systems as a whole and how they can be best managed. This book takes such a combined approach. It analyses common rainfed farming systems around the world and discusses both their strengths and ways of improving their operation and management for long term productivity, profitability and sustainability. For such desirable outcomes, the components of a system must operate together efficiently, through an understanding of the effects of external influences and inputs and of relevant interactions and other relationships. Using relevant agricultural principles and the understanding of a wide range of rainfed farming systems, this book defines principles and practices important to the effective operation and management of such systems. This is done in the context of many challenges for agriculture: climatic variability and long term climatic change; degradation of most agricultural soils; spread of diseases, pests and weeds, rapid innovations in technology and the interaction of market and political forces at both local and global levels.